Evaluation of ozone as an efficient and sustainable reagent for chalcopyrite leaching: Process optimization and oxidative mechanism - Wang, Jingxiu; Faraji, Fariborz; Ghahreman, Ahmad (Journal of industrial and engineering chemistry (Seoul, Korea), 2021)
[Display omitted] •Chalcopyrite leaching in sulfuric acid solution with ozone was studied.•Ozone leaching mechanism is changed by increased temperature.•Ferric sulfate addition decreased copper recovery by inhibiting ozone diffusion.•All different oxidative leaching follows shrinking core model by mixed control.•Ozone is a highly efficient, economic, green, and sustainable reagent. Chalcopyrite is the main copper-bearing mineral and is refractory to oxidative leaching. There are many investigations to optimize copper extraction from this mineral but most of the processes are energy intensive and environmental threatening. Ozone at low concentration is an efficient reagent for high extraction of copper from chalcopyrite, which is also ecofriendly. This paper presents a comprehensive investigation on the process optimization for both copper and iron extraction from chalcopyrite using ozone. The following variables were tested during 48-h leaching periods: temperature, ferric sulfate, ozone and sulfuric acid concentrations, solid/liquid ratio, and leaching time. Ozone leaching recovered 100% of the copper from chalcopyrite at 25 °C without addition of ferric. The overall reaction kinetics followed the shrinking core model by mixed control of diffusion through the product layer and chemical reactions. The proposed leaching mechanism was verified via various characterization techniques. Green chemistry metrics were evaluated, and the optimized process was demonstrated to be environmentally attractive. Ozone leaching appears to have strong potential as a “green” and technically feasible method to leach copper from chalcopyrite.